Diversification or specialization: Measuring the impact of high-speed rail connection on technological diversity in China - Jun Chen; Guangzhen Guo (Journal of Innovation & Knowledge (JIK), 2023)
Technological diversification and specialization have important roles in explaining volatility, innovation, income inequality, exports, and related concerns; however, the relationships between transportation improvement and technological diversification and specialization remains unexplored. Using Chinese city-level panel data, we investigate the impact of China's high-speed rail (HSR) connection on technological diversity using the difference-in-differences method and instrumental variable regressions. The results demonstrate that HSR connection leads to reductions in technological diversity, particularly in core cities, cities along the four longest HSR lines, and cities that were initially diversified. The findings indicate that HSR connection is conducive to technological specialization rather than diversification, offering new insights for understanding the relationship between transportation improvement and innovation and determining that HSR connection spurs intra-industry knowledge spillovers more than inter-industry knowledge spillovers.
Keywords: 650; High-speed rail; Innovation; Knowledge spillovers; Technological diversification; Technological specialization